Project scheduling in distributed and dynamic environments - Song, Wen (2018)
Project scheduling is an important task of modern business management. Classic project scheduling approaches assume a centralized and deterministic environment. However, today's manufacturing and management have entered into a more open and dynamic environment, which jeopardizes the effectiveness of traditional approaches. Two important practical factors that cause this issue are: 1) distributed management, where multiple decision makers with conflicting individual objectives are involved in the scheduling process, and 2) execution uncertainty, where projects are executed in dynamic environments containing various uncertainty sources. It is non-trivial to incorporate these practical factors since they make the project scheduling problems, which are already computationally intractable, even harder to solve. In this thesis, we provide effective approaches to address the two above-mentioned practical factors.